MODEL PENYEBARAN KRIMINALITAS DENGAN PENGARUH KEBIJAKAN KRIMINAL SEBAGAI PENCEGAHAN PADA SITUASI KRISIS EKONOMI - Muhammad Audri Indraputra; Anita Triska; Nursanti Anggriani (LPPM Universitas Bina Bangsa, 2023)
Crime is behavior that violates the law and social norms so that people oppose it which can occur due to environmental factors, namely the imitation of criminality and individual economic factors, can be prevented by criminal policies, and can increase in certain situations, one of which is the economic crisis. The mathematical model of the spread of crime is built by considering individual economic factors which are implemented as work and non-work compartments, crime imitation factors which are implemented as the rate of crime affected, and criminal policy factors as an obstacle to crime. Based on the model that has been built, the equilibrium point and its stability, the basic reproduction rate, population dynamics, and conditions that can describe the influence of criminal policy and the economic crisis on the crime rate are determined. The model has one non-endemic equilibrium point and one non-negative endemic equilibrium point which can reach a stable condition. Numerical simulations show that population dynamics using parameter values and initial compartments obtained from various sources are stable towards an endemic equilibrium point, criminal policies can reduce crime rates, and economic crises can increase crime rates.